Silver Nanoparticles Supported on Chitosan as a Green and Robust Heterogeneous Catalyst for Direct Synthesis of Nitrogen Heterocyclic Compounds under Green Conditions - Seyedeh Fazileh Fazileh Hamzavi; Shahla Jamili; Morteza Yousefzadi; Ali Mashinchian Moradi; Narges Amrollahi Biuki (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
The catalytic efficiency of silver nanoparticles supported on chitosan as a green, robust, and efficient nanocatalyst for the direct synthesis of biologically active compounds, such as: imidazole derivatives as well as pyrazine scaffolds through multi-component reactions strategy, have been demonstrated. In this work, imidazole derivatives were achieved via pseudo four-component reactions by utilization of benzaldehydes, benzils, anilines, and ammonium acetate under solvent-free conditions. Moreover, pyrazine scaffolds were synthesized through a three-component reaction of phenylenediamine derivatives, isocyanides and various ketones in water. The main advantages of this protocol are the  reusability of the catalyst, operational simplicity, mild reaction conditions, and high-yielding.